O crédito agropecuário como um elemento da questão agrária : análise do crédito agropecuário público no estado de Mato Grosso - Moreira, Marcelo Carlos (2012)
In the process of conservative modernization of the Brazilian agriculture, since the 1960s, the agricultural credit played a central role. There was a consolidation of the capitalist agriculture, strengthening the economic, social and political power of the landlordism which in order to increase the production, continued the historical expropriation of the indigenous and squatter lands. In this study we analyzed the hypothesis that “the public agricultural credit is one of the structuring elements of the Brazilian agrarian issue and its concentration reflects and contributes to the maintenance of the concentration of the land, the wealth and political power that configures the agrarian structure”. In order to evaluate it we use as a territorial sample the state of Mato Grosso which was studied within the national scale context. The agricultural credit is the main source of funding of the Brazilian agriculture and its ownership is extremely unequal. In Mato Grosso, the properties of 200 ha or over occupy 90% of the lands and own 94% of the credit. The properties with less than 200 ha occupy 9% of the area and own 6% of the total credit. Half of the national agricultural credit is concentrated in properties with areas above 1.000 ha. If we take into account the land ownership structure, these properties represent only 1,6% of the total number of the rural properties. Facing the other information and analyses which demonstrate a historical negligence in relation to the peasant agriculture in Brazil, there is a correlation between the concentration of land and credit.